PENGARUH TINGKAT SUKU BUNGA KREDIT TERHADAP PERMINTAAN KREDIT USAHA MIKRO PADA PT BANK MALUKU & MALUT KANTOR CABANG UTAMA DI KOTA AMBON - Maitimu, Agustin Gebriel; Kainama, Maryoni S; Tomasoa, Theodora F (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2025)
This study aims to determine the effect of credit interest rates on the demand for micro-enterprise credit at PT Bank Maluku & Malut's main branch office in Ambon City. This research is a descriptive quantitative study. The data collection technique used is documentation, using financial report data, specifically credit interest rate reports and notes on micro-enterprise credit demand reports at PT Bank Maluku & Malut's main branch office in Ambon City. Data analysis techniques in this study include simple linear regression, classical assumption testing, and hypothesis testing. The results of this study indicate that variable (X) or credit interest rates have a significant effect on the demand for micro-enterprise credit at PT Bank Maluku & Malut's main branch office in Ambon City because the sig value of 0.002 is smaller than 0.05 and the calculated t-value is -3.207 < t-table 1.6710. Based on these results, it shows that if there is an increase in the credit interest rate variable (x) by 1%, there will be a decrease in the demand for micro-enterprise credit variable (y), and vice versa.